2005
DOI: 10.1186/cc3540
|View full text |Cite
|
Sign up to set email alerts
|

Renal blood flow in sepsis

Abstract: Introduction To assess changes in renal blood flow (RBF) in human and experimental sepsis, and to identify determinants of RBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(83 citation statements)
references
References 163 publications
2
78
1
2
Order By: Relevance
“…This finding is consistent with the recent advances in the pathophysiological understanding of sepsis-induced AKI in humans: the classic paradigm is that decreased blood flow in septic patients is the principal pathophysiological cause of AKI. However, volume resuscitation and renal vasodilators have little effect [30] and renal blood flow was found to be normal or even increased in resuscitated sepsis patients [31,32]. In addition, acute tubular necrosis is rarely found in septic kidneys [33].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the recent advances in the pathophysiological understanding of sepsis-induced AKI in humans: the classic paradigm is that decreased blood flow in septic patients is the principal pathophysiological cause of AKI. However, volume resuscitation and renal vasodilators have little effect [30] and renal blood flow was found to be normal or even increased in resuscitated sepsis patients [31,32]. In addition, acute tubular necrosis is rarely found in septic kidneys [33].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in spite of conflicting animal studies, Langenberg et al [91] reported only 3 studies in humans that have directly calculated renal blood flow in septic AKI via invasive measurements. All 3 studies demonstrated that septic AKI is characterized by renal arterial vasodilation and preserved overall renal blood flow [92,93,94].…”
Section: Endotoxin Effects On Renal Functionmentioning
confidence: 99%
“…Indeed, glomerular filtration rate and cellular perfusion can diminish even if the overall renal blood flow is improved due to imbalanced vascular resistance between the afferent and efferent arterioles, regional microvascular flow rates, or renal venous congestion [91,96]. Renal and central venous pressures are often augmented in septic patients as a potential effect of the so-called fluid challenge of the first hours after intensive ICU admission.…”
Section: Endotoxin Effects On Renal Functionmentioning
confidence: 99%
“…We recently performed a comprehensive review of electronic reference libraries, using sepsis and acute renal failure as the key words and limiting it to animal models [12]. We found approximately 160 original articles.…”
Section: The Primacy Of Renal Blood Flowmentioning
confidence: 99%